Execution and invention death penalty discourse in early Rabbinic and Christian cultures - Berkowitz, Beth A.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2006)
Beth Berkowitz explores modern scholarship on the ancient Rabbinic death penalty and offers a fresh perspective using the approaches of ritual studies, cultural criticism and Talmudic source criticism. She argues that the death penalty was used by the early Rabbis in an attempt to assert their authority.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capital punishment in rabbinical literature; Rabbinical literature -- History and criticism; Capital punishment -- Religious aspects -- Judaism; Capital punishment -- Religious aspects -- Christianity; Electronic books